Review Brain Tumor Detection Using Image Processing Techniques - Lohare, DN; Telgade, R; Manza, RR (International Journal of Computer Sciences and Engineering, 2025)
Brain Tumor is a cluster of irregular cells which grows inner side of the brain by abandoned growth in tissues of the brain. Which wants to be treated, if left unprocessed it extent over a wide area in other parts of the brain too? It is very complicated and tough to detect the brain tumor in primary phase as there are very few or no symptoms in the beginning stages. Medical image processing and its segmentation is an active and attractive area for researchers. It has reached at the incredible place in diagnosing tumors after the discovery of CT and MRI. MRI is a valuable tool to detect the brain tumor and segmentation is performed to carry out the useful portion from an image. Detecting Brain tumor using Image Processing techniques involves four stages namely Image Pre-Processing, Image segmentation, Feature Extraction, and Classification.